2019
DOI: 10.1002/bio.3705
|View full text |Cite
|
Sign up to set email alerts
|

A triazole‐based fluorescence probe for detecting Hg2+ ions and its biological application

Abstract: A new compound, ethyl 5-phenyl-2-(p-tolyl)-2H-1,2,3-triazole-4-carboxylate was successfully introduced and synthesized as a novel rhodamine B derivative named REPPC, and characterized by 1 H nuclear magnetic resonance (NMR), 13 C NMR, and high resolution mass spectrometry (HRMS). It showed an obvious fluorescence and UV-visible light absorption enhancement towards Hg 2+ ion without interference from common metal ions in N,N-dimethylformamide-H 2 O (pH 7.4). The spirolactam ring moiety of rhodamine in REPPC was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Excessive accumulation of heavy metal ions (such as Cr 3+ , Hg 2+ , Cd 2+ , Cu 2+ , Ag + ) in water and soil with rapid industrial growth is causing harm to the health of living organisms and human body. [ 1–5 ] Among these heavy metal ions, copper ion is special as it is an essential trace element in the human body. Deficiency in copper ions can cause impaired growth, osteoporosis, and bone abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive accumulation of heavy metal ions (such as Cr 3+ , Hg 2+ , Cd 2+ , Cu 2+ , Ag + ) in water and soil with rapid industrial growth is causing harm to the health of living organisms and human body. [ 1–5 ] Among these heavy metal ions, copper ion is special as it is an essential trace element in the human body. Deficiency in copper ions can cause impaired growth, osteoporosis, and bone abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that mercury poisoning can occur when urinary mercury level exceeds 0.05 mg/L. Therefore, development of fluorescent probes that meet the above detection limit criteria for systematic detection of Hg 2+ would be highly important. …”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] There is therefore an urgent need to develop new Hg 2+ detection methods that are sensitive and low cost, with a rapid response, and are applicable to aqueous solutions. To this end, many studies on the development of various mercury‐sensing‐based techniques, including fluorescence, [ 16 ] localized surface plasmon resonance (LSPR), [ 17 ] electrochemical, [ 18 ] colourimetry [ 19 ] have been undertaken. Among the reported sensors, colorimetry has witnessed very rapid development because of the advantages of rapid detection, easy manipulation, and little or no required instrumentation.…”
Section: Introductionmentioning
confidence: 99%